1977
DOI: 10.1192/bjp.130.3.265
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Daily Recordings from the Moos Menstrual Distress Questionnaire

Abstract: Nineteen volunteers completed a Moos Menstrual Distress Questionnaire daily for a period exceeding one menstrual cycle. The data were analysed, using a least mean square method of fitting sine waves. The fact that the results obtained on this group are essentially those found by other workers looking at the menstrual cycle suggests that this may be a useful method for assessing menstrual distress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

1980
1980
1998
1998

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(21 citation statements)
references
References 6 publications
2
19
0
Order By: Relevance
“…Retrospective reports of premenstrual changes are supported by daily ratings in some studies but not in others (26,27). In the experience of the authors, reports of severe changes are confirmed more frequently than are reports of mild changes.…”
Section: Issues Not Addressed In the Current Study And Needing Furthementioning
confidence: 70%
“…Retrospective reports of premenstrual changes are supported by daily ratings in some studies but not in others (26,27). In the experience of the authors, reports of severe changes are confirmed more frequently than are reports of mild changes.…”
Section: Issues Not Addressed In the Current Study And Needing Furthementioning
confidence: 70%
“…The influence of the so-called extraneous variables-age, irregularity of periods, parity, pregnancy, marital status, oral contraceptives-have not been documented beyond controversy. To-date, we have many conflicting reports on the effects of using oral contraceptives (combination pills) alone on premenstrual tension (19,20,24). Our aim here is limited.…”
Section: Introductionmentioning
confidence: 80%
“…Coppen and Kessel (5) had found that the premenstrual symptoms of irritability, tension, swelling, and menstrual irregularity were positively correlated with the neuroticism scale. Sampson and Jenner (19) did not observe any such relationship. Rees (17) observed that premenstrual tension was more frequent in neurotic than in normal subjects, and that its intensity correlated with neurotic predisposition.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The MDQ has been widely used in the United States and in Europe to document the prevalence and severity of PMS symptoms (4,(9)(10)(11)(12). Psychometric studies have documented the reliability and content validity of the MDQ, and indicate that it has a high level of consistency and test-retest reliability (8,13,14).…”
Section: Instrumentsmentioning
confidence: 98%